The Fresnel Diffraction: A Story of Light and Darkness - Aime, C. (EDP SCIENCES, 2013)
This book is a collection of 19 articles which reflect the courses given at the Collège de France/Summer school "Reconstruction d'images − Applications astrophysiques" held in Nice and Fréjus, France, from June 18 to 22, 2012. The articles presented in this volume address emerging concepts and methods that are useful in the complex process of improving our knowledge of the celestial objects, including Earth.